2004
DOI: 10.2337/diabetes.53.10.2676
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Scan for Metabolic Syndrome and Related Quantitative Traits in Hong Kong Chinese and Confirmation of a Susceptibility Locus on Chromosome 1q21-q25

Abstract: T he clustering of multiple metabolic abnormalities, including insulin resistance, glucose intolerance, hypertension, dyslipidemia, and obesity, in particular central obesity, is known as syndrome X, or metabolic syndrome (MES) (1-3). MES is a major health problem characterized by increased morbidity and mortality. The prevalence of MES in the general adult population varies from 10 -13% in mainland Chinese (4,5) to 20 -30% in U.S. whites and Mexican Americans (6,7). However, direct comparison of these rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 46 publications
7
69
0
Order By: Relevance
“…We were unable to replicate the results from that study by again showing evidence of linkage for metabolic syndrome on chromosome 1 at 169.5-181.5 cM and on chromosome 2 at 44.1-57.3 cM. However, we did observe a significant QTL on chromosome 16 at 45 cM (LOD=4.29 and LOD [1] =3.27 for 1 h insulin and AUC insulin), similar to the reported region at 45.2-65.4 cM (with LOD=1.75, 1.61 and 1.25 for metabolic syndrome, HOMA-IR and HDL-cholesterol respectively) in Hong Kong Chinese [7].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We were unable to replicate the results from that study by again showing evidence of linkage for metabolic syndrome on chromosome 1 at 169.5-181.5 cM and on chromosome 2 at 44.1-57.3 cM. However, we did observe a significant QTL on chromosome 16 at 45 cM (LOD=4.29 and LOD [1] =3.27 for 1 h insulin and AUC insulin), similar to the reported region at 45.2-65.4 cM (with LOD=1.75, 1.61 and 1.25 for metabolic syndrome, HOMA-IR and HDL-cholesterol respectively) in Hong Kong Chinese [7].…”
Section: Discussionsupporting
confidence: 82%
“…In search for the genetic loci for metabolic syndrome (as a categorical diagnosis) and its related traits, many studies have been conducted in different populations [11,14,16,38,39], including Chinese living in Hong Kong [7]. We were unable to replicate the results from that study by again showing evidence of linkage for metabolic syndrome on chromosome 1 at 169.5-181.5 cM and on chromosome 2 at 44.1-57.3 cM.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Goldin et al [37] summarised 12 studies reporting QTLs related to the metabolic syndrome components; the QTLs were located mostly on chromosomes 1, 3, 5, 6, 7, 10, 14 and 17. Some studies have tried to locate genes responsible for the metabolic syndrome as a composite variable [38][39][40][41]. Given that genetic correlations between the endophenotypes of metabolic syndrome were weak to moderate as suggested from this study, finding genes for the metabolic syndrome as a composite variable may not be a good strategy.…”
Section: Discussionmentioning
confidence: 94%
“…It should also be noted that several family-based studies have identified genetic linkage of some metabolic syndrome traits to 22q. The HyperGEN Network found linkage of diabetes status to 22q12.1 in hypertensive patients [7]; markerD22S683 near CYP2D6 on 22q was found to be linked and associated with type 2 diabetes in Northern Ontario Oji-Cree [8]; and the plasma HDL-cholesterol (HDL-c) level was linked to 22q in the Hong Kong Family Diabetes Study [9].…”
Section: Introductionmentioning
confidence: 99%